Foreign meat identification by DNA breed assignment for the Chinese market - Rogberg Muñoz, Andres; Shuai, Wei; Ripoli, María Verónica; Boli, Guo; Carino, Mónica Herminia; Castillo, Nadia Sabiela; Villegas Castagnasso, Egle Etel; Liron, Juan Pedro; Morales Durand, Hernán F.; Melucci, Lilia Magdalena; Villarreal, Edgardo Leopoldo; Peral Garcia, Pilar; et al. (Elsevier, 2019)
Methods for individual identification are usually employed for traceability, whereas breed identification is useful to detect commercial frauds. In this study, Chinese Yellow Cattle (CYC) samples plus data from six Bos taurus breeds, two Bos indicus breeds, and one composite breed were used to develop an allocation test based on 22 microsatellites. The test allowed discriminating all foreign breeds from the CYC, although some CYC individuals were wrongly allocated as Limousin or Holstein, probably due to the recent introduction of these breeds into China. In addition, CYC evidenced a previously reported Zebu cline (south–north) and a possible structure within the B. taurus component that should be confirmed. An independent test performed with meat samples of unknown breed origin from Argentina allocated 92% of them to either Angus, Hereford, or their crossbreed, but none was identified as CYC. We conclude that the test is a suitable tool to certify meat of foreign breed origin and to detect adulterations of CYC beef labeled as imported meat.